«Спогади про подорож до Сибіру, перебування в Березові та Саратові» Єви Фелінської: генологічний аспект - Білявська, Вікторія Сергіївна (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті «Спогади про подорож до Сибіру, перебування в Березові та в Саратові» Є. Фелінської проаналізовано особливості жанрової організації тексту, притаманні мемуаристичній літературі Правобережної України доби романтизму; досліджено механізми і характерні риси взаємодії структурних частин та принципи їх функціонування. «The Memories of the Journey to Siberia, Staying in Berezovo and Saratov» by E. Felinska, an outstanding writer and public figure, occupies a prominent place in the canon of memoirs’ texts of Polish literature of Right-Bank Ukraine of the Romantic era. In the article peculiarities of the text’s genre organization, typical for memories by E. Felinska, the mechanisms and characteristics of the interaction of structural parts and principles of their functioning were analized. The memoirs’ paradigm of Ukrainian-Polish borderland of the Romantic era, which began to fill up with new modifications arising from the «loosening» of the constant genological system of the Enlightenment and the impact of further development, both fiction and other related scientific disciplines, that contributed to an active genre interactions.
Keywords: Є. Фелінська; мемуаристика; жанр; спогади; щоденник; асиміляція жанрів